Meningkatkan Kesadaran Pendidikan Seks di Era Digital Bagi Siswa Madrasah Ibtidaiyah - Pratama, Loviga Denny; Al-ahdab Villah, Mohammad Hafas; Badriyah, Fa’iqotul (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2021)
The majority of the Sentulan Village community, Probolinggo Regency, have children at the MI level. As a result of the Covid 19 pandemic, these children almost every day have to operate smartphones and the internet as communication tools as their media in online learning (via online). The community also realizes that their children will be at risk of being exposed to various adult content. So it is considered important to equip children with the right information about gender and sexuality based on their age and stage of development to answer the challenges of the rapid growth of the digital era. Through community service, this is carried out with students of the Islamic University Zainul Hasan Genggong through the Real Work Lecture Program (KKN) and using the ABCD (Asset-Based Community-driven Development) method. The results can be concluded that sex education is very important to be given since children are at an early age. In addition, after the program was completed, there was a positive change in the behavior of the children of Sentulan Village, Probolinggo Regency.